Influence of triboelectric processes on friction characteristics of braking devices of technological transport. - Криштопа, С.І. (Problems of Tribology, 2017)
As a result of the carried out investigations of the friction properties of metal-polymer friction pairs of brake de-vices under laboratory and operating conditions the laws of change are established for triboelectric interaction: the values of the contact difference of the potentials of friction pairs "grey cast iron - polymers" of drum-block and band-block brakes from surface temperature of linings and specific loads; the dynamic coefficient of friction from the values of circulating thermal and tribological currents; the values of the braking moments produced by individual friction units and the total brake mo-ments from the change in the generated tribological currents in the contact of the two-layer "metal-polymer" structures. Ex-perimental studies of triboelectric processes were carried out on a specially created laboratory stand that modelled band-block brake of technological transport and on the serial universal brake stand of the KI-8964 GOSNITI model which makes it pos-sible to investigate metal-polymer pairs of friction of drum-block and disc brakes. Measurement of tribological current was carried out with the help of the n-ampere meter F-195, and the potential difference - with the help of the analog-to-digital converter USB Oscilloscope II. The number of experiments performed was sufficient to obtain results with a confidence probability of 0,95.Key words: metal-polymer friction pairs, drum-block brake, band-block brake, tribosystem triboelectric processes.